Physiotherapy Management for Cases of Iliotibial Band Syndrome in Indonesian Para Athletics Athletes : Case Report - Farhan Sufi Hibatul Azizi; Suryo Saputra Perdana; Amalia Nur Azizah (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Iliotibial band syndrome (ITBS) is an overuse syndrome that commonly causes knee pain and is common in athletics. The prevalence of ITBS in runners ranges from 5%-14%, with a higher prevalence in women (16%-50%) than in men (50%-81%). ITBS can limit Indonesia's athletic performance due to pain on the side of the knee during running, walking and jumping. The aim of this study was to evaluate the physiotherapy management for ITBS cases in Indonesian para-athletics. This research is a descriptive case study involving one client with a participatory observation method. The physiotherapy intervention involved Shock Wave Therapy (SWT) and Static Stretching Exercise. The subject of the study was 22 year old national para athlete with height 182 cm, weight 70 kg, and BMI 21.1 in the ideal category. The patient came to the physiotherapy clinic of NPC Indonesia on 20 August 2023 with complaints of pain in the outer side of the right knee. Physical examination showed normal results except for pain examination using Numeric Rating Scale (NRS), where silent pain 2/10, tenderness 4/10, and motion pain 5/10 were found. The diagnosis of ITBS dextra was confirmed through specific examination. After six physiotherapy sessions with SWT and Static Stretching Exercise, there was a significant decrease in pain and an increase in functional activity in ITBS patients. Patients are advised to undergo physiotherapy regularly, do stretching exercises before and after activities, and compress with warm water if experiencing pain.